The Role of Principal Supervision in Improving Teacher Performance - Ely Surayya; Sumirah Sumirah (Yayasan Literasi Kita Indonesia, 2021)
Principal supervision aims to improve teacher performance. Next is teacher performance, namely strengthening teacher characteristics in an effort to improve the quality of work life, as stated by Sellar and Maura, which states that teacher characteristics have traditionally been assessed as a desired indicator or as teacher quality, the latter is closely related to the impact of values, attitudes and understanding as a professional practitioner educator. For teachers to be effective in the information age, they need to get to know students more about their backgrounds and learning styles. Teachers must be effective and act positively in the classroom to improve educational outcomes. In order to do this they must have the will to enhance cognitive learning inthe process.